1985
DOI: 10.1007/bf00054216
|View full text |Cite
|
Sign up to set email alerts
|

The origin of selected lunar geochemical anomalies: Implications for early volcanism and the formation of light plains

Abstract: The Apollo orbital geochemistry, photogeologic, and other remote sensing data sets were used to identify and characterize geochemical anomalies on the eastern limb and farside of the Moon and to investigate the processes responsible for their formation. The anomalies are located in the following regions: (I) Balmer basin, (2) terrain northeast of Mare Smythii, (3) near Langemak crater, (4) Pasteur crater, (5) terrain northwest af MiIne basin, (6) northeast of Hendefeev basin, (7) north and northeast of Koroiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 11 publications
4
48
0
Order By: Relevance
“…The region contains Undarum and Spumans mare deposits and the Balmer plains, but is composed of predominantly non-plains terra units. The results of the study presented here provide further evidence for the compositional diversity of the lunar highlands (Taylor, 1975;Head, 1976;Bielefeld et al, 1977;Clark et al, 1978;Haines et al, 1978;Hawke and Head, 1978;Schonfeld and Bielefeld, 1978;Clark and Hawke, 1981;Maxwell and Andre, 1981;Andre and El Baz, 1981;Hawke et al, 1985). The enhancements in mafic elements, particularly Mg and either Ti or Fe, and in Th in plains units of the Balmer basin region tends to support the contention that the primary sources of this heterogeneity are episodes of volcanism, earlier than or contemporary with mare volcanism, in areas now mapped as highlands.…”
Section: Interpretationssupporting
confidence: 62%
See 1 more Smart Citation
“…The region contains Undarum and Spumans mare deposits and the Balmer plains, but is composed of predominantly non-plains terra units. The results of the study presented here provide further evidence for the compositional diversity of the lunar highlands (Taylor, 1975;Head, 1976;Bielefeld et al, 1977;Clark et al, 1978;Haines et al, 1978;Hawke and Head, 1978;Schonfeld and Bielefeld, 1978;Clark and Hawke, 1981;Maxwell and Andre, 1981;Andre and El Baz, 1981;Hawke et al, 1985). The enhancements in mafic elements, particularly Mg and either Ti or Fe, and in Th in plains units of the Balmer basin region tends to support the contention that the primary sources of this heterogeneity are episodes of volcanism, earlier than or contemporary with mare volcanism, in areas now mapped as highlands.…”
Section: Interpretationssupporting
confidence: 62%
“…This paper presents a portion of the results of the systematic geochemical classification of lunar highland terrain (Clark, 1982;Clark andHawke, 1981, 1982a, b;Clark et al, 1978;Hawke et al, 1985). The following questions which have arisen concerning the oldest and most extensive lunar terrane, the highlands, are addressed in these studies: (1) How chemically homogeneous are the highlands on both a regional and a global scale?…”
Section: Introductionmentioning
confidence: 99%
“…Initially analyses were carried out for 25 regions previously recognized as cryptomaria (Fig. 4, Table 1) Spudis, 1979, 1983;Hawke and Spudis, 1980;Hawke and Bell, 1981;Bell and Hawke, 1984;Hawke et al, 1985Hawke et al, , 1993Hawke et al, , 2002Hawke et al, , 2005Hawke et al, , 2013Head et al, 1993;Blewett et al, 1995;Mustard and Head, 1996;Antonenko, 1999a,b;Giguere et al, 2003;Campbell and Hawke, 2005;Lawrence et al, 2008). Of these 25 proposed locations, only 20 were confirmed in this study (see Section 4.1.…”
Section: Methodsmentioning
confidence: 60%
“…High concentrations of DHCs on high-albedo smooth plains are indicative of a buried, areally extensive mare deposit. Other criteria, such as geochemical and mineralogic anomalies (e.g., Hawke and Spudis, 1980;Hawke and Bell, 1981;Bell and Hawke, 1984;Hawke et al, 1985;, intermediate albedo surfaces, and Bouger gravity anomalies (Sori et al, 2013), have also been developed to aid in the identification and mapping of cryptomaria.…”
Section: Introductionmentioning
confidence: 99%
“…Head et al 1993;Greeley et al 1993;Blewett et al 1995;Mustard & Head 1996) and orbital geochemical observations (e.g. Hawke & Spudis 1980;Hawke et al 1985). These studies have shown that if cryptomaria are included, the total area covered by mare deposits exceeds 20% of the lunar surface, compared with about 17% of typical mare deposits alone (Head 1976;Antonenko et al 1995).…”
Section: Volcanic Landformsmentioning
confidence: 95%